The Tax is right ; Making it work ; Yoyoy Villame yearns [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
Examines the new taxes on beer proposed by the Congress. NPA commander and founder, Dante Buscayno leads a farmers' cooperative in Tarlac. Yoyoy Villame talks about his life and his music.